2018
DOI: 10.3390/jintelligence6020025
|View full text |Cite
|
Sign up to set email alerts
|

How to Think Rationally about World Problems

Abstract: I agree with the target essay that psychology has something to offer in helping to address societal problems. Intelligence has helped meliorate some social problems throughout history, including the period of time that is covered by the Flynn effect, but I agree with Sternberg that other psychological characteristics may be contributing as well, particularly increases in rationality. I also believe that increasing human rationality could have a variety of positive societal affects at levels somewhat smaller in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Empirical research findings on human rationality, however, suggest otherwise, showing that literacies are fundamental but not sufficient for individual readiness. Several models of human cognition showed that information processing roughly follows two separate routes: either a peripheral, fast route with mental shortcuts and simple rules (i.e., heuristics) or a central, cognitively effortful route with a reflective, metacognitive outlook on the available information ( Sundar, 2008 ; Stanovich, 2009 , 2018 ). Having access to these two processing routes (or systems, Stanovich, 2009 ) is highly adaptive, but overreliance on the heuristic route can lead to multiple cognitive biases ( Sundar, 2008 ; Stanovich, 2009 ).…”
Section: Open Access Literacies and Rational Thinkingmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical research findings on human rationality, however, suggest otherwise, showing that literacies are fundamental but not sufficient for individual readiness. Several models of human cognition showed that information processing roughly follows two separate routes: either a peripheral, fast route with mental shortcuts and simple rules (i.e., heuristics) or a central, cognitively effortful route with a reflective, metacognitive outlook on the available information ( Sundar, 2008 ; Stanovich, 2009 , 2018 ). Having access to these two processing routes (or systems, Stanovich, 2009 ) is highly adaptive, but overreliance on the heuristic route can lead to multiple cognitive biases ( Sundar, 2008 ; Stanovich, 2009 ).…”
Section: Open Access Literacies and Rational Thinkingmentioning
confidence: 99%
“…Having access to these two processing routes (or systems, Stanovich, 2009 ) is highly adaptive, but overreliance on the heuristic route can lead to multiple cognitive biases ( Sundar, 2008 ; Stanovich, 2009 ). Therefore, people who are sufficiently literate in terms of health and statistical knowledge may nevertheless suffer such cognitive biases ( Stanovich, 2018 ) and make irrational choices as to whether, for example, to vaccinate themselves and/or their children against COVID-19 due to the anti-vaccination messages. The messages are typically communicated through affect-laden, salient imagery focused on vaccine toxicity and its side effects and consequently tend to trigger fast, heuristic processing ( Okuhara et al, 2020 ).…”
Section: Open Access Literacies and Rational Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Swedes may see masks as something that makes it difficult to judge whether a person can be identified as rational, responsible, and so able to contribute to a functioning society. It may be that this skepticism regarding who is capable of caring for herself and fellow citizens [23] contributed during 2020 to mask “underuse” in Sweden. So, what appears to mainly have determined face mask use during the first wave of the Covid-19 pandemic in Sweden is a belief in scientific evidence and reliance on institutionalized knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Morsanyi & Handley (2012) have obtained the first empirical evidence of type 1 logic in syllogistic reasoning tasks. Later,Trippas et al (2016) supported the implicit nature of the sensitivity to logical validity with conditionals, disjunctions and also syllogisms.Other authors (such asStanovich, 2018b) shared the previous proposal, considering that the autonomous mind includes normative rules and rational strategies that are automatic by previous practice. In this sense, the "normative mindware" can compete with other non-normative answers and could be modulated by other factors (for example, the feeling of rightness).As has been seen, De Neys' research group has defended the presence of distinct intuitive responses: heuristic and logical intuitions.…”
mentioning
confidence: 98%